DIGITALISASI UMKM: PERAN NILAI-NILAI ISLAM DAN KEARIFAN LOKAL ALON-ALON WATON KELAKON DALAM ADAPTASI TEKNOLOGI: MSME Digitalization: The Role of Islamic Values and Local Wisdom Alon-Alon Waton Kelakon in Technology Adaptation - Dwita Setiyani (tesco publisher, 2025)
This study aims to explore how Islamic business ethics and the Javanese cultural philosophy of Alon-Alon Waton Kelakon (slow and steady) influence digital technology adaptation strategies among Micro, Small, and Medium Enterprises (MSMEs). Amid the global push for rapid digital transformation, culturally rooted MSMEs often exhibit resistance or slow down, which is often misinterpreted as lagging behind. This study employed a qualitative method with a case study approach in the Batik Industry Center in Central Java. Data were collected through in-depth interviews with 15 business owners and participant observation. The results show that the Alon-Alon Waton Kelakon principle does not act as a barrier, but rather as a prudence-based filtering mechanism to mitigate the risk of technology investment failure. Islamic values, particularly Siddiq (honesty) and Amanah (responsibility), are integrated into technology adoption to ensure that digitalization does not erode the quality of transactional relationships. Furthermore, the spirit of mutual cooperation serves as a social safety net in the transfer of technological knowledge among business actors. This research makes a theoretical contribution by offering a “Reflective Technological Adaptation” model that balances the speed of innovation with the sustainability of ethical and cultural values.